Critical significance of supply chain resiliency during and post-pandemic: Analysing the impact of applied supply chain strategies on achieving resilient supply chain in the manufacturing sector - Bhardwaj, Gaurav (Digital Repository of Theses - SSBM Geneva, 2024)
The COVID-19 pandemic underlined the significance of supply chain flexibility, especially in the manufacturing industry, which experienced highly negative impacts from disruptions. This work aims to explore the effectiveness of different supply chain approaches used during and after the pandemic to increase supply chain resilience. To this end, the study extends a wide-ranging literature review to identify how several elements, including digital technology applications, risk management, and supply chain flexibility, have been used to manage disruption and sustain business operations. The study also examines the relationship between resilience and operational performance which encompasses both short-term contingency measures as well as long-term recovery plans in the face of disruptions occasioned by the pandemics. By doing so, the research outlines factors that enhance supply chain resiliency and provides guidance to manufacturing firms that would like to enhance the resiliency of their supply chains to future proof from shocks around the globe. The outcomes proved to be quite helpful in understanding these strategies, and indicated the increasing need for a strategic approach to risk management in supply chain in order to maintain high performance over time, given the current global volatility. Furthermore, the research aims to analysing the impact of supply chain resilience on operational performance, focusing on long-term configurations for post-pandemic performance and short-term measures in response to disruptions caused by the pandemic. This research provides guidelines that manufacturing firms can use to strengthen their supply chain and prepare for potential future shocks and disruptions by evaluating the effectiveness of the above listed strategies. It also gives an understanding of the main characteristics of supply chain for strength and the essential drivers that foster such strength. The research offers important insights into the suitability of these strategies and underscores the importance of addressing supply chain risks before they materialize and of maintaining superior performance in a world that increasingly poses threats to supply chains.